A 2PJ/Pixel/Direction MIMO Processing Based CMOS Image Sensor for Omnidirectional Local Binary Pattern Extraction and Edge Detection - Xiaopeng Zhong; Qian Yu; Bermak, Amine; Chi-Ying Tsui; Law, May-Kay (2018 IEEE Symposium on VLSI Circuits, 2018)
This paper presents an energy-efficient multi-mode CMOS image sensor featuring omnidirectional local binary pattern extraction (LBP-E), edge detection (ED) and normal imaging. A mixed-signal 4-pixel simultaneous group computation (GC) scheme is developed to extract complete 8-direction LBP and edge. High-speed and energy-efficient column-parallel GC is achieved with the proposed group-switchable multi-input multi-output (MIMO) comparator. The reconfigurable mixed-signal processing circuits ensure multi-mode operations with minimum area overhead. Fabricated in 0.18μm CMOS, the prototype sensor consumes 6.5μW and 12.7μW at 30fps for full 8-direction LBP-E and ED, achieving the state-of-the-art FoMs of 2.0 and 3.9 pJ/pixel/direction, respectively. Measurement results also demonstrate high-accuracy on-chip LBP-E, with a histogram similarity of up to 97.5% compared to the DSP one.